The role of qualea multiflora on mammary tumour cells and immune system - Carli, Camila Bernardes de Andrade; Quilles, Marcela Bassi; Vilegas, Wagner [UNESP]; Carlos, Iracilda Zeppone [UNESP] (My University, 2013)
Species of the genus Qualea are used by the Brazilian public as a natural anti-inflammatory. Based on this evidence, we evaluated the effects of terpene fractions (Î²F and TF) obtained from Qualea multiflora on nitric oxide production (Griess assay), cytokines (IL-1, IL-10, IL-12, and TNF-a) and the transcription factor NF-ÎºB by peritoneal macrophages. Since there is a relationship between inflammation and cancer, the cytotoxicity of Î²F and TF against mammary tumoural cell lineage, and macrophages was evaluated. Inhibition levels close to 90% of the production of NO, IL-1, IL-12 and TNF-a; about 32% of NF-ÎºB; and a large stimulation of IL-10 production (close to the positive control) by peritoneal macrophages were observed in response to Î²F and TF which are correlated with anti-inflammatory activity. Additionally, the samples showed exceptional cytotoxic activity against tumoural cells but not against macrophages. Since anti-inflammatory activity is important in tumour inhibition, further examination of potential anti-cancerous activity of Qualea multiflora is warranted.